The effect of cluster thinning, cluster tipping, cluster shredding and defoliation at the flowering on the vegetative and generative vine performance from Kékfrankos Cv. - Fazekas, I.; Göblyös, J.; Bisztray, Gy. D.; Zanathy, G. (International Journal of Horticultural Science, 2012)
The cluster thinning is a method of the yield regulation.With the removal one part of the clusters, the yield pro leaf area will be lower, hereby the grape and wine quality will be improved. The regulation of the yield can lead to further advantages: the ratio of the vegetative and generative performance of the vines will improve, the condition of the plants will better, the number of the physiological diseases can be reduced and the growth of the shoots and roots can be promoted. The grape growers make the cluster thinning almost exclusive by creating one cluster shoots. Usually the upper clusters are removed, because the sugar content of these second or third clusters will be lower. The cluster thinning is an easy task, can be done without special skills. It is an effective method improving wine quality, but its use can lead to other problems. The grapes try to compensate the removed clusters. Therefore the clusters will be bigger and thicker, but more sensitive to bunch rot. Moreover the treatment is expensive, because it needs manual work. It is worth to get acquainted and try the new yield regulation methods, which can help to avoid the occurring problems. Our aim is to show the results of our experiment, which was carried out in Eger, examining the red grape cultivar Kékfrankos. During our 4 years long experiment we compared the effects of cluster thinning, cluster shredding, cluster tipping and defoliation at the flowering, on the vegetative and generative vine performance.